2014
DOI: 10.1016/j.cardfail.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Regulation Therapy via Left or Right Cervical Vagus Nerve Stimulation in Patients With Chronic Heart Failure: Results of the ANTHEM-HF Trial

Abstract: Chronic open-loop ART via left- or right-side VNS is feasible and well tolerated in HFrEF patients. Safety and efficacy measures are encouraging and warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
255
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(277 citation statements)
references
References 40 publications
8
255
0
8
Order By: Relevance
“…The INOVATE-HF trial (with 436 patients implanted with VNS stimulators) designed as an outcome trial failed to show benefit of VNS in the hard endpoints of death and heart failure events whilst there again appeared to be some subjective symptomatic improvement. A smaller ANTHEM-HF trial (Premchand et al 2014) (with 60 patients implanted with VNS stimulators) showed some positive results similar to the initial pilot study. These clinical results have significantly reduced the momentum, which was built in the clinical translation of VNS in patients with heart failure and hence would not help in addressing the question whether VNS has a favourable effect on ventricular arrhythmia events.…”
Section: Indirect Antiarrhythmic and Non-arrhythmic Beneficial Effsupporting
confidence: 52%
“…The INOVATE-HF trial (with 436 patients implanted with VNS stimulators) designed as an outcome trial failed to show benefit of VNS in the hard endpoints of death and heart failure events whilst there again appeared to be some subjective symptomatic improvement. A smaller ANTHEM-HF trial (Premchand et al 2014) (with 60 patients implanted with VNS stimulators) showed some positive results similar to the initial pilot study. These clinical results have significantly reduced the momentum, which was built in the clinical translation of VNS in patients with heart failure and hence would not help in addressing the question whether VNS has a favourable effect on ventricular arrhythmia events.…”
Section: Indirect Antiarrhythmic and Non-arrhythmic Beneficial Effsupporting
confidence: 52%
“…Preliminary results using VNS showed promise and stimulation of the right cervical vagus nerve with pulses synchronised to the cardiac cycle improved NYHA class, quality of life scores and left ventricular end-systolic volume (Schwartz et al, 2008). Larger studies subsequently showed VNS was associated with a significant improvement in cardiac function, quality of life scores and exercise performance (De Ferrari et al, 2011;Premchand et al, 2014).…”
Section: Anatomy Of the Auricular Branch Of The Vagus Nervementioning
confidence: 99%
“…The cuff electrode is routinely used in the clinical setting for vagus nerve stimulation (VNS), which has been shown to be effective in the management of epilepsy [31,104], resistant depression [127], blood pressure control [110], as well as prevention of heart failure in patients with reduced ejection fractions [32,43,113]. Additionally, the InspireÂŽ hypoglossal nerve stimulator, a Food and Drug Administration (FDA)- Fig.…”
Section: Cuff Electrodesmentioning
confidence: 99%